RFID Spatio-Temporal Data Management - WANG Yonghui; XU Jingke; WANG Shoujin (Institute of Advanced Engineering and Science, 2013)
Radio-frequency Identification (RFID) technology promises to revolutionize the way we track items in supply chain, retail store, and asset management applications. The size and different characteristics of RFID data pose many interesting challenges in the current data management systems. In this paper, we provide a brief overview of RFID technology and highlight a few of the spatio-temporal data management challenges that we believe are suitable topics for exploratory research. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2213